An Apology of Drunkenness in the Works of Galaktion Tabidze and Edgar Poe - Sordia, Luara (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2025)
The American master of words Edgar Poe and the king of Georgian poets Galaktion Tabidze often referred to drunkenness of being, life, fire, wine, hope, but this metaphorical statement does not refer to drunkenness of alcohol, but to the faith of Christian religion, because being, life, fire, wine, hope are divine are the divine names according to Holy Scripture. Galaktion Tabidze's poetry draws attention to the concept of drinking with ancient wine, precious wine, immortal wine, blue wine, being, and fire. In the Holy Scripture, "old, purified wine," being (living), and enlightening fire are divine names, as are vineyard and vine. Galaktion Tabidze, a great master of symbolic-metaphorical thinking, addressed these images from a religious perspective and emphasized their connection with faith. The poet considered art, not wine, to be the "best narcotic" ("Narcotics and Art"). In the works of the great American poet and master of words, Edgar Allan Poe, "drinking with white flame," "hope," "greatness," and "the moon" are mentioned with a similar meaning. "Flame, fire, hope, glory" are divine names, while "moon" is the name of the Mother of God, and in this case, too, the connection with faith is alluded to. In this scientific study, based on the comparative research method, the concept of the apologetics of the throb in the works of Galaktion Tabidze and the American poet and novelist Edgar Allan Poe is analyzed. Both poets, using the concept of throb, struggled with painful memories, feelings of insurmountable loneliness, and sought an uncertain destiny in faith.